Terceiro setor: um ator estratégico para o desenvolvimento humano Fundação Dona Mindoca Rennó Moreira- Escola Técnica de Eletrônica Francisco Moreira da Costa-FMC-ETE: Santa Rita do Sapucaí- MG-2013 - Moussallem, Márcia (2014)
This thesis has as its theme the role of a third sector organization in human development in a municipality. Dona Mindoca Rennó Moreira Foundation - Technical School of Electronics Francisco Moreira da Costa (FMC ETE) was chosen as a research study case. This organization is located in Santa Rita do Sapucaí, Minas Gerais State, which is a third sector organization with innovative actions in the field of technological education. Was formulated as a hypothesis that the FMC-ETE while a third sector organization innovated and transformed, through their actions in the educational field, the economic, social, political and cultural profile of the municipality of Santa Rita do Sapucaí, turning into a strategic actor in promoting human development of this municipality. The general objective aimed to analyze the innovative actions of the Foundation since its beginning in 1959. The theoretical references comprise the concepts of third sector and human development based on classical authors of contemporary areas of study in social sciences and social service. It was adopted an exploratory approach methodology of quantitative and qualitative research for the case study of FMC-ETE. Indicators of human development were analyzed and conducted interviews with 25 residents of the city including: alumni, entrepreneurs, directors and employees of FMC -ETE, directors and teachers of INATEL and FAI. The research main results were: actions and innovative initiatives for development are not exclusive of state and private enterprises as the classical theories use to state, but also can be the result of the initiatives of third sector organizations. The strong investment in education made by FMC-ETE provided the human development of the city, collaborating for the formation of a culture of active citizenship and social participation